PENGARUH ALOKASI DANA DESA (ADD) TERHADAP PENINGKATAN PENDAPATAN SEKTOR PERTANIAN DI KABUPATEN JOMBANG - Muafiqie, Humaidah; Tianto, Erys (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
Purpose of providing immediate relief of ADD is a stimulant or aid funds to finance incentives to encourage village government program supported by the participation of community self-help mutual assistance in carrying out the activities of government and community empowerment. The purpose of giving direct assistance Village Allocation Fund include tackling poverty, reduce unemployment, and welfare of the community, Improving the quality of development planning and budgeting at the village and community empowerment, improving rural infrastructure development, encourage community self-reliance and mutual cooperation. From the analysis it can be seen that if there is influence Village Allocation Fund (ADD) to improve household incomes in Jombang. Furthermore, from the results of t-test analysis showed that the Village Fund Allocation can not be a government program to increase incomes in general.